Effect of Ethanol Concentration on Antibacterial Activity of Bligo Fruit Extract (Benincasa hispida Thunb) to Salmonella typhi - Mubarak, Fhahri; Sartini, Sartini; Purnawanti, Dia (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Bligo fruit (Benincasa hispida Thunb) is one of medicinal plants that used to cure typhoid fever which caused by Salmonella typhi bacteria. The aim of this research is to find ont the effect of ethanol concentration as a solvent from Bligo fruit (Benincasa hispida Thunb) extracts as an antibacterial, especially to Salmonella typhi. This simplicia was being extracted with 96% ethanol, 70% ethanol, and 50% ethanol by using maceration method for 3x24 hours. The antibacterial activity test was done by diffusion of agar method to the MHA medium by obserring the resistor zone which formed from 96% ethanol, 70% ethanol and 50% ethanol. The diametres that have been obtained are 6,815 mm for 96% ethanol, 25,223 mm for 70% ethanol while for 50% ethanol there is no resisten zone can be seen. From the result canbe conclude that the best concentration of ethanol that has a great potencial as resistor to Salmonella typhi bacteria is the Bligo fruit (Benincasa hispida Thunb) extracts of 70% ethanol.Key words: Bligo fruit (Benincasa hispida Thunb), Antibacterial, Salmonella typhi.